2019
DOI: 10.1152/ajpendo.00431.2018
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone signaling and action in obese versus lean human subjects

Abstract: Growth hormone (GH) levels are blunted in obesity, but it is not known whether this relates to altered GH sensitivity and whether this influences the metabolic adaptation to fasting. Therefore, we investigated the effect of obesity on GH signal transduction and fasting-induced changes in GH action. Nine obese (BMI 35.7 kg/m2) and nine lean (BMI 21.5 kg/m2) men were studied in a randomized crossover design with 1) an intravenous GH bolus, 2) an intravenous saline bolus, and 3) 72 h of fasting. Insulin sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…Since rodents do not express GH-V, the high secretion of the pituitary version of GH, especially during late pregnancy (23,32,77), may be associated with the gestational insulin resistance. It is well known that GH from pituitary also possesses potent diabetogenic effects and inhibits insulin action (19,37,38,44,45). Thus, our findings provide new evidence indicating that central GH action regulates insulin sensitivity during pregnancy, since ablation of GHR in the entire brain or in LepR-expressing cells protects mice from gestational insulin resistance (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…Since rodents do not express GH-V, the high secretion of the pituitary version of GH, especially during late pregnancy (23,32,77), may be associated with the gestational insulin resistance. It is well known that GH from pituitary also possesses potent diabetogenic effects and inhibits insulin action (19,37,38,44,45). Thus, our findings provide new evidence indicating that central GH action regulates insulin sensitivity during pregnancy, since ablation of GHR in the entire brain or in LepR-expressing cells protects mice from gestational insulin resistance (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…We have repeatedly observed STAT5 activation in human skeletal muscle and adipose tissue in vivo following exogenous GH exposure together with increased mRNA expression of CISH and SOCS . 16 , 32 , 33 , 34 , 35 The present study is the first to document that sustained endogenous GH overproduction induces detectable activation of STAT5 signalling in adipose tissue, which illustrates the importance of adipose tissue as a direct GH target. We have previously reported that fatty acid infusion dampens GH-induced pSTAT5 expression in adipose tissue in healthy human subjects, 36 but the present data suggest that active acromegaly may override any such feedback suppression.…”
Section: Discussionsupporting
confidence: 53%
“…GH signaling and action has been evaluated in obese patients. Hogild et al have found that GH signaling is normal in obesity and there is increased hepatic GH sensitivity, suggesting that the blunted GH levels in obesity may protect against insulin resistance without compromising IGF-1 levels [ 54 ]. In another study Glad et al have found that GH receptor expression was decreased in subjects with obesity compared with subjects with normal weight; GH receptor was increased in response to energy restriction and decreased in response to overfeeding.…”
Section: Discussionmentioning
confidence: 99%